Dr. Gary Chapman on the marriage you always wanted - Chapman, Gary D., 1938- (Chicago : Moody Publioshers, 2005)
After the leftover wedding cake has been consumed and the thank-you notes written, the blissful couple often uncovers some jarring realities: a trail of dirty socks on the floor, conflicting opinions on how much money is too much for a bottle of shampoo and a general wonderment at the question, 'What does it mean to merge the worlds of two very different people?' In an updated version of Toward a Growing Marriage, beloved relationship expert and marriage counselor Gary Chapman offers his trademark practical wisdom on the many issues young married couples face. His basic message: to enjoy 'the marriage you've always wanted, ' we have to be the person Jesus has always wanted us to be. He looks at such areas as meaningful communication, expectations about 'who does what' around the house, and the challenges of money management. 'Your Turn' questions inspire further interaction between wives and husbands. This book makes a superb sequel to The Five Love Languages as it takes the 'next step' in making unselfish relationships a reality. - Publisher.
What is marriage for? -- "Why won't they change?" -- What love really means -- "Listen to me!" -- Who takes care of what? -- Decisions, decisions -- "You mean we have to work at sex?" -- Leaving and honoring parents -- Love and money.
Includes bibliographical references.
Keywords: Marriage -- Religious aspects -- Christianity